Synthesis and properties amphiphilic meso-arylsubstituted porphyrins - I. N. Fedulova; N. V. Novikov; O. A. Ugolnikova; N. A. Bragina; I. P. Ushakova; A. F. Mironov (Тонкие химические технологии)
Synthesis of amphiphilic meso-arylsubstituted porphyrins with hydrophobic long chain groups and with terminal carboxylic and hydroxylic groups via dipyrrolylmethanes and with the use of monopyrrolic condensation is described. The synthesized porphyrins will allow studying the influence of fragments of amphiphilic structures of porphyrins on self-aggregation of porphyrins in micellar and bilayer model membrane systems